Environmental Impoverishment, Aging, and Reduction in Mastication Affect Mouse Innate Repertoire to Explore Novel Environments and to Assess Risk - Siqueira Mendes, Fabíola de Carvalho Chaves de; Paixão, Luisa Taynah Vasconcelos Barbosa da; Diniz, Cristovam Wanderley Picanço; Sosthenes, Marcia Consentino Kronka (Frontiers in Neuroscience, 2019)
We examined in an open arena, the exploratory and locomotor activities of mature (6-month-old; 6M), late mature (12-month-old; 12M), and aged (18-month-old; 18M) mice, subjected to distinct masticatory regimens and environments. Three different regimens of masticatory activity were used: continuous normal mastication with hard pellets - HD; normal mastication followed by reduced mastication with equal periods of pellets followed by soft powder - HD/SD; or rehabilitated masticatory activity with equal periods of hard pellets, followed by powder, followed by pellets - HD/SD/HD). Under each diet regimen, half of the individuals were raised in standard cages (impoverished environment; IE) and the other half in enriched cages (enriched environment; EE). Animals behavior on the open field (OF) task were recorded by webcam and analyzed with Any Maze software (Stoelting). Independent of diet regime, 6M young mice maintained in an enriched environment where voluntary exercise apparatus is available, revealed significant less body weight than all other groups. Although body weight differences were minimized as age progressed, 18M EE group revealed intragroup significant influence of diet regimens. The locomotor and exploratory activities in OF task declined with age, and this was particularly evident in 18M HD EE mice. Although all groups kept their preference by the peripheral zone, the outcomes were significantly influenced by interactions between environment, age, and diet. We suggest that long life environmental enrichment reduces the tendency to avoid open/lit spaces (OF) and this is particularly influenced by masticatory activity. These measurements may be useful in discussions of anxiety-related tasks.